TRANSPOSITION OF THE ANTI AVOIDANCE MEASURES, ESTABLISHED IN THE COUNCIL DIRECTIVE 2009/133/EC, INTO LITHUANIAN LAW - Petkevičiūtė, Agnė (Teisė, 2016)
On 19 October 2009 The Council Directive 2009/133/EC on the common system of taxation applicable to mergers, divisions, partial divisions, transfers of assets and exchanges of shares concerning companies of different Member States and to the transfer of the registered office of an SE or SCE between Member States was adopted.Provisions of the said Directive were implemented in the Chapter IX of the Law on Corporate Income Tax in Lithuania. However Article 15 of the Directive – a means against tax avoidance – was not directly transposed into Lithuanian legislation. Thus it is not clear weather Lithuanian tax administrator could fight cases of tax avoidance in the international mergers or transfers and what means in such cases should be used. It is also not clear whether the said article of the Directive should have in general been directly transposed into national legislation.This article provides a comprehensive analysis of the article 15 of the Directive as well as addresses problem aspects of the application of the substance over form principle in the cases of international mergers and transfers in Lithuania.Having made an in-depth analysis the author of the article draws the following conclusions: wording of the Article 15 of the Directive – namely the definition of tax avoidance and valid commercial reasons, burden of proof – is unclear. The Court of Justice of the European Union does not provide much definition either. According to the Court of Justice, Article 15 of the Directive is a reflection of a general principle which states that abuse of rights is prohibited. Direct transposition of the said article into national legislation is not necessary – a general anti-avoidance rule established in the national legislation may suffice. In the case of tax avoidance in international mergers and transfers a substance over form principle could be applied in Lithuania. In the cases of tax avoidance mergers and transfers are used as a part of group of operations. In order to identify an aim to avoid tax, the whole group of operations and actual circumstances should be analysed. Substance over form principle can only be applied in the cases when there is a subjective intention to gain tax advantage as well as objective circumstances demonstrating that the purpose of the Directive was not achieved.